Pathogenic variants in the AFG3L2 proteolytic domain cause SCA28 through haploinsufficiency and proteostatic stress-driven OMA1 activation. Issue 8 (25th March 2019) - Tulli, Susanna; Del Bondio, Andrea; Baderna, Valentina; Mazza, Davide; Codazzi, Franca; Pierson, Tyler Mark; Ambrosi, Alessandro; Nolte, Dagmar; Goizet, Cyril; Toro, Camilo; Baets, Jonathan; Deconinck, Tine; et al.
Abstract : Background: Spinocerebellar ataxia type 28 (SCA28) is a dominantly inherited neurodegenerative disease caused by pathogenic variants in AFG3L2. The AFG3L2 protein is a subunit of mitochondrial m -AAA complexes involved in protein quality control. Objective of this study was to determine the molecular mechanisms of SCA28, which has eluded characterisation to date. Methods: We derived SCA28 patient fibroblasts carrying different pathogenic variants in the AFG3L2 proteolytic domain (missense: the newly identified p.F664S and p.M666T, p.G671R, p.Y689H and a truncating frameshift p.L556fs) and analysed multiple aspects of mitochondrial physiology. As reference of residual m -AAA activity, we included SPAX5 patient fibroblasts with homozygous p.Y616C pathogenic variant, AFG3L2 +/− HEK293 T cells by CRISPR/Cas9-genome editing and Afg3l2 −/− murine fibroblasts. Results: We found that SCA28 cells carrying missense changes have normal levels of assembled m -AAA complexes, while the cells with a truncating pathogenic variant had only half of this amount. We disclosed inefficient mitochondrial fusion in SCA28 cells caused by increased OPA1 processing operated by hyperactivated OMA1. Notably, we found altered mitochondrial proteostasis to be the trigger of OMA1 activation in SCA28 cells, with pharmacological attenuation of mitochondrial protein synthesis resulting in stabilised levels of OMA1 and OPA1 long forms, which rescued mitochondrial fusion efficiency. Secondary to altered mitochondrial morphology, mitochondrial calcium uptake resulted decreased in SCA28 cells. Conclusion: Our data identify the earliest events in SCA28 pathogenesis and open new perspectives for therapy. By identifying similar mitochondrial phenotypes between SCA28 cells and AFG3L2 +/− cells, our results support haploinsufficiency as the mechanism for the studied pathogenic variants.